Effect of motor control training on hip muscles in elite football players with and without low back pain - Mendis, M. D.; Hides, J. A. (Journal of Science and Medicine in Sport, 2016)
Objectives: Previous research has shown that motor control training improved size and function of trunk muscles in elite football players with and without low back pain (LBP). Imbalances in hip muscles have been found in athletes with LBP and it is not known if motor control training can change these muscles. This study investigated if a motor control intervention program affected hip muscle size in elite football players with and without LBP. Design: Panel-randomised intervention design. Methods: Forty-six players from one club in the Australian Football League (AFL) participated in a motor control training program delivered across the season as a stepped-wedge intervention design with 3 treatment arms: 15 weeks intervention, 8 weeks intervention and a wait-list control who received 7 weeks intervention toward the end of the playing season. Presence of LBP was assessed by interview and physical examination. Cross-sectional areas of iliacus, psoas, iliopsoas, sartorius, gluteus minimus, and gluteus medius muscles were measured from magnetic resonance images taken at 3 time points during the season. Results: Iliopsoas, sartorius and gluteus medius muscle size increased for players who received intervention (p < 0.05). For players with current LBP, sartorius and gluteus medius muscle size increased for those who received motor control training (p < 0.05). Conclusions: Motor control training programs aimed at the lumbo-pelvic region also benefit the hip muscles. For players with current LBP, the intervention mitigated sartorius muscle atrophy and increased gluteus medius muscle size. These findings may help guide the management of LBP in elite football players.